Jewish Life as the Main Theme of Saul Bellow’s Novels - Sinha, Arti (Journal of Advanced Research in English & Education; Vol 4 No 4 (2019): Journal of Advanced Research in English and Education, 2021)
As the most influential contemporary American literary figure, Saul Bellow is the true picture of confusion and spiritual emptiness of western society. He, in his literary career, wrote a large number of novels, which won several awards including ‘Nobel Prize’. In his novels, Bellow explores modern living condition. He depicts urban intellectuals, especially the plight of American-Jewish intellectuals and is concerned about the real need and aspirations of the modern man. How to cite this article:  Sinha A. Jewish Life as the Main Theme of Saul Bellow’s Novels. J Adv Res Eng & Edu 2019; 4(4): 6-8. DOI: https://doi.org/10.24321/2456.4370.201908